2017
DOI: 10.1017/s0954579417000190
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing executive functioning among toddlers in foster care with an attachment-based intervention

Abstract: Young children in foster care often experience adversity, such as maltreatment and lack of stability in early caregiving relationships. As a result, these children are at risk for a range of problems, including deficits in executive functioning. The Attachment and Biobehavioral Catch-up for Toddlers (ABC-T) intervention was designed to help foster parents behave in ways that promote the development of young children's emerging self-regulatory capabilities. Participants included 173 parent-toddler dyads in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 78 publications
4
70
2
2
Order By: Relevance
“…These findings are consistent with a larger body of work demonstrating positive effects of ABC on child outcomes across a range of domains (e.g., Bernard et al, ; Bick et al, ; Dozier & Bernard, ; Grube & Liming, ; Lind, Raby, Caron, Roben, & Dozier, ; Raby et al, ; Tabachnick, Raby, Goldstein, Zajac, & Dozier, ). In addition to promoting secure and organized attachments during infancy (Bernard et al, ), ABC is effective in reducing children's expression of negative affect (Lind, Bernard, Ross, & Dozier, ) and enhancing executive functioning (Lind et al, ), physiological regulation (Bernard, Hostinar, & Dozier, ), and receptive vocabulary (Raby et al, ) in early childhood for children involved in the child welfare system. During middle childhood, ABC has been shown to positively affect physiological regulation (Tabachnick et al, ) and brain development (Bick et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…These findings are consistent with a larger body of work demonstrating positive effects of ABC on child outcomes across a range of domains (e.g., Bernard et al, ; Bick et al, ; Dozier & Bernard, ; Grube & Liming, ; Lind, Raby, Caron, Roben, & Dozier, ; Raby et al, ; Tabachnick, Raby, Goldstein, Zajac, & Dozier, ). In addition to promoting secure and organized attachments during infancy (Bernard et al, ), ABC is effective in reducing children's expression of negative affect (Lind, Bernard, Ross, & Dozier, ) and enhancing executive functioning (Lind et al, ), physiological regulation (Bernard, Hostinar, & Dozier, ), and receptive vocabulary (Raby et al, ) in early childhood for children involved in the child welfare system. During middle childhood, ABC has been shown to positively affect physiological regulation (Tabachnick et al, ) and brain development (Bick et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Not incidentally, the three key caregiving dimensions linked to children’s EF (sensitivity, mind–mindedness, and autonomy–support; Carlson, 2003) have also been linked to secure attachment (Ainsworth, Blehar, Waters, & Wall, 1978; Bernier & Dozier, 2003; Whipple, Bernier, & Mageau, 2011). Further, a recent study found that children of parents who participated in the Attachment and Biobehavioral Catchup for Toddlers program showed improved EF skills following the intervention, including reduced attention problems and enhanced cognitive flexibility (Lind, Raby, Caron, Roben, & Dozier, 2017 [this issue]).…”
Section: Additional Attachment-related Child Outcomes: Executive Funcmentioning
confidence: 99%
“…As toddlers, children in the ABC intervention showed lower anger during a frustrating problem-solving task than children in the control group [41]. Finally, children in the ABC group also showed more optimal inhibitory control and cognitive flexibility several years after the intervention than children in the control group [42,43]. …”
Section: Efficacy Of Abcmentioning
confidence: 99%
“…Similar to ABC for infants, ABC-T coaches provide frequent in the moment comments to celebrate, reinforce, and scaffold parents’ behaviors with regard to each of the targets. In a randomized clinical trial, ABC-T has been found to improve foster children’s cognitive flexibility and reduce foster children’s attention problems [43]. In ongoing research, it will be critical to examine whether ABC-T reduces externalizing behaviors, such as aggression and non-compliance, in addition to the related constructs of cognitive self-control.…”
Section: Abc For Toddlersmentioning
confidence: 99%